Technology adoption model for smart urban farming-a proposed conceptual model - Zhahir, Amirul Asyraf; M Shuhud, Mohd Ilias; Mohd, Siti Munirah; Kamarudin, Shafinah; Ahmad, Azuan; Salleh, Rossly; Md Norwawi, Norita (Institute of Advanced Engineering and Science, 2024)
Technological advancements have made their way into the heart of human civilization across numerous fields, namely healthcare, logistics, and agriculture. Amidst the sprouting issues and challenges in the agriculture sector, particularly, the growing trendof integrating agriculture and technologies is roaring. The public and private sectors work hand in hand with regard to addressing these complex issues and challenges that arise, aiming for efficient and sustainable possible solutions. This study is a continuation of a previous systematic literature review; hence, the main objective is to deliver a proposed conceptual model for technology adoption specifically for smart urban farming. Innovation diffusion theory (IDT) is used as the main foundation of the proposed conceptual model, supplemented with additional factors drawn from other exisiting technology adoption models both the originals and extended versions. The outcome of the study is expected to reveal valuable insights into the components affecting the technology adoption model in smart urban farming, which will be further laid out upon in the upcoming study, offering a robust framework for future studies and applications in smart urban farming.